Benefits of Establishing a Land Bank for Development in Indonesia - Dinda Raihan; Liza Priandhini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
As mandated by Law Number 11 of 2020 on Job Creation, on 29 April 2021 the Indonesian government has enacted Government Regulation Number 64 of 2021 on Land Bank Agency (“GR No. 24/2021”). Land Bank Agency is a special agency called sui generis, formed as a transparent, accountable and non-profit Indonesian legal entity that is established by the central government to be autonomous and independent and is given rights to exercise part of the government authority to manage lands.  The Indonesian constitution has provided clear regulations regarding lands in Indonesia under Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which asserts that the power given to the earth, water and natural resources contained therein rests with the state. The state must regulate its ownership and its use. The objective of such stipulation is that all land in its entirety in the territory of the Indonesian nation’s sovereignty is used for the greatest prosperity of the people. The Indonesian government hopes that the establishment of the Land Bank Agency will ensure the availability of land for all society groups from the Indonesian people to foreign investors in the field of public interest, social interest and national development to create a fair economy. The Land Bank Agency is viewed to expedite the process in seeking lands for public interest. This article aims to give light on the function of Land Bank for national growth and public interest.